MODEL PEMILIHAN MODA DAN POTENSI PENGGUNAAN NON MOTORIZED TRANSPORT PADA MASA PANDEMI COVID-19 DI KOTA TEGAL - Pipit Rusmandani; Riandy Sholeh Setiawan; Nurul Fitriani (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2021)
This study aims to (1) determine the factors affecting the mode preference in Tegal, (2) determine the factors affecting the potential use of non-motorized transportation in Tegal, and (3) investigate the relationship model among these factors. PLS Structural Equation Modelling (SEM) method was used. The results revealed (1) socio-economic characteristics (KSE) with vehicle ownership indicators influenced the mode choice level, (2) socio-economic characteristic variables with vehicle ownership indicators, travel intention variable (MP) covering working, shopping, and worship indicators, and self-preservation behaviour variable during the pandemic affected the potential use of non-motorized transport [0.801 KSE; (R2= 0,647)] (3) the relationship model among variables [Socio-economy (KSE), purpose of travel (MP), and self-preservation behaviour (PMD)] was =0,280 KSE+ 0.317 MP-0.175 PMD; (R2=0,2570)